Uji Berbagai Konsentrasi Plant Growth Promoting Rhizobacteria Akar Bambu dan Dosis Pupuk Kandang Sapi Terhadap Pertumbuhan Vegetatif Tanaman Jagung: Testing Various Concentrations of Bamboo Root Plant Growth Promoting Rhizobacteria and Doses of Cow Manure on the Vegetative Growth of Corn Plants - Yusran, Muhammad; Munawir; Zaman , Nur (Universitas Hasanuddin, 2024)
This study aims to optimize the growth of maize plants (Zea mays L.) through the application of various concentrations of Plant Growth Promoting Rhizobacteria (PGPR) and doses of cow manure. PGPR is known to enhance nutrient availability and improve plant resilience to environmental conditions, while cow manure serves as an organic nutrient source that supports plant growth. The research was conducted in the village of Lekopancing, Tanralili district, Maros regency, at an elevation of 0-40 meters above sea level. The study was designed using a factorial randomized block design (RBD). The first factor was the concentration of PGPR with 4 levels: without PGPR (P0), PGPR 10 ml l-1 water (P1), PGPR 20 ml l-1 water (P2), and PGPR 30 ml l-1 water (P3). The second factor was the dose of cow manure, consisting of 4 levels: without manure (K0), cow manure at 15 tons ha-1 (K1), 25 tons ha-1 (K2), and 35 tons ha-1 (K3). The observed parameters included plant height (cm), number of leaves (leaves), flowering time (DAP), leaf area (cm2). The results showed no interaction between the application of PGPR and cow manure for all observed parameters. However, various concentrations of PGPR had a highly significant effect on all measured parameters, with PGPR at a concentration of 20 ml l-1 water yielding the best results for plant height (176.49 cm), number of leaves (15.46 leaves), leaf area (516.99 cm2), and 50% flowering time (52.33 DAP).